Analisa Kritis Implementasi Akad Wadi’ah dalam Perbankan Syariah - Mushlih Candrakusuma; Mohammad Ghozali (Study Program Ekonomi Syari'ah, Sekolah Tinggi Agama Islam Muhammadiyah Tulungagung, 2016)
Islamic banking does not only have the opportunity, but also a variety of problems. Among these current accounts and savings products sharia, which is based on contract wadi'ah. In its application, the trust receives deposits of Islamic banks in storing and channeling funds so that people can benefit optimally. In principle, the wadi'ah uptake of a deposit in the form of any legal limits. Wadi'ah applied in Islamic banking, more relevant to the contract qard (of debt). Islamic banking implement the agreement or contract wadi qard'ah. The purpose of Islamic law (maqasid al-shari'ah) on guaranteeing the consignment (hifz al-mal), embodied in the product save deposit box. In the save deposit box, a treasure entrusted to the bank, stored in a special storage area, which is maintained by the bank. At the primary level (al-daru Riyah), maintaining wealth is something fundamental, so it must be fought for the sustainability of maintenance. At the secondary level (al-hajjiyah), save deposit box is one means of facilitating bank to keep up the maintenance of the property.